2016
DOI: 10.1186/s12711-016-0261-6
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality of genomic information and performance of the Algorithm for Proven and Young for different livestock species

Abstract: BackgroundA genomic relationship matrix (GRM) can be inverted efficiently with the Algorithm for Proven and Young (APY) through recursion on a small number of core animals. The number of core animals is theoretically linked to effective population size (N e). In a simulation study, the optimal number of core animals was equal to the number of largest eigenvalues of GRM that explained 98% of its variation. The purpose of this study was to find the optimal number of core animals and estimate N e for different sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(97 citation statements)
references
References 38 publications
8
89
0
Order By: Relevance
“…This was successfully demonstrated for several purebred Table 4. Regression coefficients (b1) of adjusted phenotypes on genomic EBV, for different groups of validation animals (purebred animals L1 and L2, and their crosses C) with a different source of phenotypes available, shown for traits 1 (T1) and 2 (T2), under the first model (M1; 2-trait animal model without the distinction between the lines) and second model (M2; when that trait was separated into 3 traits based on the line of the animals) populations in different species (e.g., Pocrnic et al, 2016b); however, the application of this concept for crossbred/multibreed contexts was unclear. Bradford et al (2017) found, by simulating a purebred population, that any core definition is robust in populations with complete pedigree; otherwise, selecting core animals randomly across multiple generations gives desirable accuracies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was successfully demonstrated for several purebred Table 4. Regression coefficients (b1) of adjusted phenotypes on genomic EBV, for different groups of validation animals (purebred animals L1 and L2, and their crosses C) with a different source of phenotypes available, shown for traits 1 (T1) and 2 (T2), under the first model (M1; 2-trait animal model without the distinction between the lines) and second model (M2; when that trait was separated into 3 traits based on the line of the animals) populations in different species (e.g., Pocrnic et al, 2016b); however, the application of this concept for crossbred/multibreed contexts was unclear. Bradford et al (2017) found, by simulating a purebred population, that any core definition is robust in populations with complete pedigree; otherwise, selecting core animals randomly across multiple generations gives desirable accuracies.…”
Section: Resultsmentioning
confidence: 99%
“…Me seems to be the key parameter of the algorithm for proven and young (APY) (Misztal et al, 2014), which reduces the computational cost of the inversion of genomic relationship matrix (G) by shrinking the dimensionality of genomic information (Misztal, 2016). For large populations, such dimensionality was close to 4NeL and corresponded to the number of eigenvalues explaining 98% variability of G (Pocrnic et al, 2016a(Pocrnic et al, , 2016b. The same study showed that Me varies from about 4k for pigs and chickens to over 10k for cattle.…”
Section: Take Down Policymentioning
confidence: 99%
“…Misztal (2016) and Pocrnic et al (2016a,b) propose that the number of animals required to explain almost all GRM variance equals M e and can be estimated as the number of largest Eigen values explaining nearly all variance. Pocrnic et al (2016b) applied this to Holstein and Jersey cattle populations, where they required more than 10,000 Eigen values to explain 98% of the variance. This number was substantially larger than values for M e obtained in our study by either the GRM or cross-validation and would have resulted in an underestimation of the prediction accuracy.…”
Section: Predicting M E From the Grmmentioning
confidence: 99%
“…An average Ne of 145 was reported in the early generations of the NCCCWA rainbow trout selective breeding program and was expected to decline with selection [45]. The estimated Ne in this population is comparable to that estimated in other livestock species; Jersey cattle (Ne = 101), Angus cattle (Ne = 113), Holstein cattle (Ne = 149) [46] and a commercial rainbow trout population (Ne = 155) [24], and it is considerably larger than the Ne estimated for cat sh (Ne = 27) [22], swine (Ne = 32), and chicken (Ne = 44) [46]. Chromosome 22 had the largest effective population size (Ne = 180) followed by chromosome 24 (Ne = 171).…”
Section: Linkage Disequilibrium and Effective Population Sizementioning
confidence: 56%